Efficiency is the Goal, Workload is the Reality: Organizational Restructuring, Job Description, and KPI Misalignment at PT WKB Indonesia - Zahrannisa Nur Tresnantari; Trias Setiawati (UTSAHA: Journal of Entrepreneurship, 2026)
constraints, yet its human consequences at the operational level remain underexplored, particularly in small-to-medium-sized enterprises within developing economies. This study examines the restructuring implemented at PT WKB, an Indonesian edutech company, focusing on employee perceptions of the restructuring process, job description adjustments, and the post-restructuring key performance indicator system. A descriptive qualitative approach was employed through a single case study design, with data collected from six purposively selected informants via semi-structured interviews, internal documents, and observation, and analyzed using the interactive model of Miles, Huberman, and Saldana. Findings indicate that while the restructuring achieved structural efficiency through workforce reduction and hierarchy flattening, it simultaneously produced workload intensification, role ambiguity, and a persistent misalignment between formal performance indicators and employees' actual contributions. Employees demonstrated adaptive tolerance rather than overt resistance, absorbing expanded responsibilities while experiencing strain from volatile directives and diminished autonomy. The study introduces adaptive tolerance as a distinct behavioral response in resource-constrained restructuring contexts and identifies the temporal lag between structural change and performance framework revision as the primary mechanism of KPI misalignment, offering practical implications for human resource practitioners managing organizational transitions.